THE CONCEPT OF INDIVIDUAL RISK IN THE FORMATION AND FEATURES OF THE COURSE OF VIBRATION DISEASE - Елена Леонидовна Смирнова; Елена Леонидовна Потеряева; Владимир Николаевич Максимов; Ирина Алексеевна Несина (Медицина в Кузбассе, 2020)
The analysis of gene-molecular and biochemical markers of early development and adverse course of vibration disease in the post-contact period is presented. The results of studying the frequencies of genotypes and alleles of the rs11562975 polymorphism of the TRPM8 gene, rs1801133 (C677T) of the MTHFR gene in patients with early and late development of vibration disease are presented. The analysis of indicators of neutrophil biocidicity depending on the timing of the formation of vibration disease for the purpose of predicting the course of the disease in the post-contact period.